Antioxidant, Anti-Alzheimer’s, anticancer, and cytotoxic properties of peanut oil: in vitro, in silico, and GC-MS analysis - Djeghim, Hanène; Benouchenne, Djamila; Mokrani, El Hassen; Alsaeedi, Huda; Cornu, David; Bechelany, Mikhael; Barhoum, Ahmed (Frontiers in Chemistry, 2024)
Introduction Peanut oil is valued for its mild flavor, rich phytochemical content, therapeutic potential, and associated health benefits. This study aims to analyze the chemical composition, antioxidant properties, and anti-Alzheimer’s potential of Algerian peanut oil using both experimental and computational approaches. The goal is to evaluate its suitability for pharmaceutical applications, particularly for its antioxidant, anti-Alzheimer, and anticancer properties. Methods The chemical composition of the peanut oil was determined using Gas Chromatography-Mass Spectrometry (GC-MS). Antioxidant activity was assessed through DPPH and CUPRAC assays, while enzyme inhibition was evaluated using butyrylcholinesterase (BChE) inhibition assays. In silico molecular docking studies were conducted to predict interactions between key compounds and BChE. Additionally, physicochemical properties were evaluated using Lipinski’s rule of five, and cytotoxicity was tested against various cancer cell lines, including melanoma (A2058 and SK-MEL-1), non-small cell lung cancer (NCI-H838), and leukemia (H9). Results GC-MS identified 20 chemical compounds in the peanut oil, with oleic acid as the predominant compound (41.98%). The antioxidant activity showed an IC50 value of 265.96 ± 14.85 μg/mL in the CUPRAC assay. BChE inhibition was moderate, with 36.47% ± 3.71% enzyme inhibition at 200 μg/mL. Molecular docking studies highlighted 6-methyl octahydro-coumarin with a docking score of −15.86 kJ/mol against BChE, although it was less potent than Galantamine (−23.4 kJ/mol). Physicochemical analysis revealed that oleic acid and palmitic acid exhibit logP values of 5.71 and 5.20, respectively, indicating drug-like potential. Cytotoxicity assessments demonstrated that oleic acid, palmitic acid, and stearic acid were effective against melanoma and lung cancer cells, while oxiraneoctanoic acid, 3-octyl, showed significant activity against leukemia cells. Discussion and conclusion The results demonstrate that peanut oil possesses notable antioxidant, anti-Alzheimer, and anticancer properties. The high concentration of oleic acid, alongside moderate butyrylcholinesterase (BChE) inhibition and strong cytotoxic effects on various cancer cell lines, highlights its potential as a therapeutic agent. While 6-methyl octahydro-coumarin exhibited favorable docking scores, its lower effectiveness compared to Galantamine suggests that further optimization is required for enhanced efficacy. These findings underscore the potential of peanut oil in pharmaceutical development, with compounds like oleic acid and oxiraneoctanoic acid emerging as promising candidates for continued research and drug development. Peanut oil from Algeria holds significant promise for future applications in antioxidant, neuroprotective, and anticancer therapies.